PENGARUH KUALITAS PELAYANAN DAN ORIENTASI PELANGGAN TERHADAPKEPUASAN NASABAH PADA PT.BANK MANDIRI - Hadi Purnomo; Yohanes Fery Cahaya; Annathasia Annathasia (Sekolah Tinggi Manajemen IMMI, 2020)
The purpose of this study was to determine the effect of Service Quality and Customer Orientation on Customer Satisfaction at PT. Bank Mandir. This study uses a descriptive research design, while the type of research is quantitative research with a questionnaire method. The study population was TVRI employees who were customers at PT. Bank Mandiri Jakarta, while the sample or research respondents were 55 respondents, which were conducted using accidental sampling (convenience sampling) techniques. The analytical tool used is the correlation test, regression and hypothesis testing. The results showed that: (1) There was a positive and significant relationship between Service Quality and Customer Satisfaction, (2) There was a positive and significant relationship between Customer Orientation and Customer Satisfaction (3) The F Test results showed that the regression model was feasible to use to predict all variables are independent of the dependent variable.